2018
DOI: 10.3390/ijerph15061107
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and Disability Profile of Children with Microcephaly Associated with Congenital Zika Virus Infection

Abstract: Introduction: The increase in the number of cases of microcephaly in Brazil and its association with the Zika virus (ZIKV) is a global public health problem. The International Classification of Functioning Disability and Health (ICF) model is a powerful tool and extremely relevant in managing disability. Objective: Describe the functioning profile of children with microcephaly associated with ZIKV in two states of northeastern Brazil. Methods: This is a descriptive cross-sectional study. The sociodemographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 39 publications
3
62
1
17
Order By: Relevance
“…However, six months after, the number of mothers who interrupted breast milk supply to infants was expressive. A previous study has shown that 47.1% of children with microcephaly associated with congenital zika virus infection were exclusively breastfed [21]; a result higher than 36.6% identified in the present investigation. erefore, the hypothesis adopted in this study that children affected by this condition will present changes in the exclusive breastfeeding pattern was confirmed.…”
Section: Discussioncontrasting
confidence: 69%
“…However, six months after, the number of mothers who interrupted breast milk supply to infants was expressive. A previous study has shown that 47.1% of children with microcephaly associated with congenital zika virus infection were exclusively breastfed [21]; a result higher than 36.6% identified in the present investigation. erefore, the hypothesis adopted in this study that children affected by this condition will present changes in the exclusive breastfeeding pattern was confirmed.…”
Section: Discussioncontrasting
confidence: 69%
“…Translating clinical information into ICF qualifiers in Brazil: The qualifiers to obtain the functional profile were generated through sensitive, reliable and validated instruments in Brazil [ 34 ], such as: Pediatric Evaluation of Disability Inventory (PEDI); Gross Motor Function Measure (GMFM—88); Visual Analog Scale (EVA); Infant Sleep Questionnaire (ISQ); Modified Ashworth Scale and Goniometry. Most of these measures are recommended in the ICF-based toolbox of measures aligning with the content of the CP core sets [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several podcasts have been prepared in Spanish and Portuguese (https://www.youtube.com/playlist?list=PLyMdWRhymqKDjyWzdfkVimSKmBt0jcMrE) commenting on key topics highlighted in DMCN Virtual Issues such as participation, activity and exercise therapies, and the transition to adulthood. Our members reported that having scientific material accessible in their own language helps in overcoming ‘environmental barriers’ in scientific publishing; (2) ALDID members are leading several projects in the region, applying ICF‐based tools for childhood‐onset disabilities such as cerebral palsy, autism spectrum disorder, and attention‐deficit/hyperactivity disorder, as well as ongoing work describing profiles of functioning and disability of children affected by congenital Zika virus in northern Brazil; and (3) Guided by the ICF, ALDID colleagues in Uruguay are creating care pathways to provide standardized evidence‐based services and interventions for young children in the region (the project is endorsed by UNICEF, Pan American Health Organization, and the Ministry of Health in Uruguay).…”
mentioning
confidence: 99%